Evaluating The Effectiveness of the Kidogo Model in Empowering Women and Strengthening Their Capacities To Engage in Paid Labor Opportunities Through The Provision of Quality Childcare: A Study Protocol for an Exploratory Study in Nakuru County, Kenya - Okelo, Kenneth; Nampijja, Margaret; Muyingo, Sylvia; Onyango, Silas; Kitsao-Wekulo, Patricia (Humanities and Social Sciences Communications, 2022)
Worldwide, there is a wide gap between what women can contribute to the economy and what they actually contribute. One of the main barriers to women’s engagement in the labor market and productivity at work is the societal expectation that they should take care of their children in addition to meeting the demands of employment. Furthermore, those in informal employment face difficulties due to long working hours and environments that are not appropriate for childcare. To address this, Kidogo runs an innovative “Hub & Spoke” model for low-income communities. Here, we present a study protocol aimed at evaluating whether the provision of quality childcare opportunities for working women through the Kidogo model is feasible and acceptable and whether it contributes to improvements in their incomes and productivity at work. The study reported in this protocol which is currently ongoing, employed a quasi-experimental design with two study arms: primary caregivers who use childcare services were recruited into the intervention (n = 170) and comparison groups (n = 170). Both groups are being followed up for one year. We are using a mixed-methods approach. Appropriate statistical methods including a difference-in-differences (DID) estimator will be used to analyze the effects of the intervention. We expect that the intervention will improve the quality of childcare services which in turn will improve the incomes of the center providers. We expect that providing improved childcare services will enhance women’s economic empowerment.
Keywords: women; childcare